KETAHANAN PANGAN PENDUDUK DI PULAU JAWA: PENDEKATAN VECTOR ERROR CORRECTION MODEL - I made Yoga Prasada; Moh Wahyudi Priyanto; Yahya Shafiyuddin Hilmi (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2020)
Food security over the past few decades has been a hot topic discussed in Indonesia. Food security can indirectly reflect the level of welfare of a household in a region. Various factors can influence the level of food security, both in the short term and in the long term. Therefore, this research was conducted with the aim to find out the factors that influence the food security of the population in the short term and in the long term. The data used in this study are secondary data sourced from the Central Bureau of Statistics (BPS) in 2008-2017, namely data on food and non-food expenditure, real per capita income, agricultural land area, real sugar prices, real beef prices, and real rice prices. The data were analyzed using the VECM (Vector Error Correction Model) model. The results showed that in the short-term the factors that influence food security are income per capita real lag 1, real sugar prices lag 1, and real beef prices lag 1, while the factors that influence food security in the long-term are per capita income 1, agricultural area lag 1, real sugar 1 lag price, real beef price lag 1, and real rice price lag 1.